2014
DOI: 10.5012/bkcs.2014.35.10.3059
|View full text |Cite
|
Sign up to set email alerts
|

Butyrolactones Derivatives from the Fermentation Products of an Endophytic Fungus Aspergillus versicolor

Abstract: Two new butyrolactones, asperphenol A (1) and B (2), together with four known butyrolactones (3-6) were isolated from the fermentation products of an endophytic fungus Aspergillus versicolor. Their structures were elucidated by spectroscopic methods including extensive 1D-and 2D-NMR techniques. Compounds 1-6 were also tested for their anti-tobacco mosaic virus (anti-TMV) activities. The results showed that compound 2 exhibited high anti-TMV activity with inhibition rate of 46.7%. The other compounds also exhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…In addition, the other 2D data can further confirm the prenyl group to be located at C-5 00 , the phenolic hydroxy group at C-4 00 and another methoxy group at C-3 00 . Compound 1 showed the Cotton effects at 225 and 316 nm in the CD spectrum, and the optical rotation valve of þ 65.8, respectively, which was similar to those of the known compound Ye et al 2014), indicating the presence of R configuration at C-4 in 1.…”
Section: Resultssupporting
confidence: 62%
See 2 more Smart Citations
“…In addition, the other 2D data can further confirm the prenyl group to be located at C-5 00 , the phenolic hydroxy group at C-4 00 and another methoxy group at C-3 00 . Compound 1 showed the Cotton effects at 225 and 316 nm in the CD spectrum, and the optical rotation valve of þ 65.8, respectively, which was similar to those of the known compound Ye et al 2014), indicating the presence of R configuration at C-4 in 1.…”
Section: Resultssupporting
confidence: 62%
“…Therefore, 1 must possess one aliphatic ring in addition to two aromatic rings. The typical carbon signals (d C 169.1 s, 139.5 s, 126.3 s, 85.8 s, 40.0 t and 170.2 s) indicated that 1 should be a phenyl butyrolactone derivative Ye et al 2014). A detailed comparison of the NMR data of 1 with those of the known compound, terrephenol A ) revealed that the only difference was due to the absence of a phenolic hydroxy group and the appearance of a methoxy group (d C 56.0 q, d H 3.81 s) in 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Butyrolactone-I was obtained as a yellowish oil by repeated column chromatography of the fermentation extract of marine fungal strain A. terreus XWC21-10. Its NMR and specific optical rotation data are listed as following and compared with a previous report [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…The results showed that 33 exhibited high anti-TMV activity with an inhibition rate of 46.7% compared with ningnanmycin (30.6 inhibition %). The other compounds also exhibited anti-TMV activities with inhibition rates in the range of 21.8-28.4% [40]. Also, the anti-TMV activities of 1, 3, 16, 35, 36, and 74 were evaluated using the half-leaf method.…”
Section: Antiviral Activitiesmentioning
confidence: 99%